2017
DOI: 10.5114/ms.2017.70345
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sclerosis: patient-reported quality of life in the Świętokrzyskie Region

Abstract: Introduction: Comprehensive epidemiologic data for multiple sclerosis (MS) in Poland are limited. Aim of the research: To analyse patient-reported quality of life and selected clinical and socio-demographic factors of patients registered in the Świętokrzyskie Cohort of the Polish Registry of Multiple Sclerosis (RejSM). Material and methods: Participants were residents of Świętokrzyskie Province, and the data were collected between January 1 st 2014 and December 31 st 2015 by the RejSM web portal. After registr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 29 publications
3
13
0
Order By: Relevance
“…The results showed that the EDSS was most employed for assessment of functional impairment. [25][26][27][28][29][30][31][32][33][34][35] As expected, the number and severity of symptoms and associated impairment appeared to play a crucial role in QoL. Fatigue, 28 29 39 40 42-52 cognitive impairment, 39 50 52 53 63 66 67 and pain, 35 39 50 51 55 56 in particular, were the focus of a large number of studies and were confirmed as important risk factors.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…The results showed that the EDSS was most employed for assessment of functional impairment. [25][26][27][28][29][30][31][32][33][34][35] As expected, the number and severity of symptoms and associated impairment appeared to play a crucial role in QoL. Fatigue, 28 29 39 40 42-52 cognitive impairment, 39 50 52 53 63 66 67 and pain, 35 39 50 51 55 56 in particular, were the focus of a large number of studies and were confirmed as important risk factors.…”
Section: Discussionmentioning
confidence: 57%
“…Functional impairment as assessed by the Expanded Disability Status Scale (EDSS) level was one of the leading causes of diminished QoL. 25–35 Disease duration, 30 31 progressive type, 26 36 37 progressive MS onset 38 and relapses in the last 3 months were further relevant factors negatively affecting QoL. 26 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…fatigue, muscle weakness, changes in menstruation, pain, anxiety, depression, urinary incontinence, and intestinal problems decrease chance of independence and ability to effectively participate in the society and interfere with ability to work, pursue leisure activities, and carry on usual life roles of employment (8,9). Physical, psychological and social effects have a signi cant impact on the quality of life and health of these patients (10,11). Dealing with the unique physical and psychological stressors associated with being in close contact (living with or caring for) a loved one with MS, marital quality is considered to be an important factor (12) .Lower relationship satisfaction, relationship distress, sexual dysfunction, and low quality of life are often reported by the couples, one of whom is affected by MS, as compared to normal couples (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…These scales allow the monitoring of a patient's responses to treatment and application of various forms of therapy. They are characterised by high sensitivity to changes, and compared to global scales, apart from the typical domains of life, they also include examples of actions or functions which might have been negatively affected by an injury or disease [13,14].…”
Section: Introductionmentioning
confidence: 99%